PRAKIRAAN KEBUTUHAN ENERGI LISTRIK KABUPATEN BERAU - Abdul Aziz Ansahri; Fitriani Fitriani (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2019)
Forecast or (forecast) is basically conjecture or prediction regarding the occurrence of an event or events in the future. Forecasts can be qualitative (not shaped figure) and quantitative (form number). Qualitative Forecast difficult to obtain a good result because the variables are very relative. Quantitative forecasts divided into two: the single forecasts (point forecast) and the forecast interval (interval forecast). In this research, the author forecast the number of customers and the need for electrical energy in Berau Regency in East Kalimantan Province. By using DKL 3.01 to forecast and project electrical energy needs in Berau Regency. The result of this final project is the estimated calculation of customer number and electricity requirement of Berau Regency from 2018 until 2027. The average increase of customer growth amount is 4.77%. As well as an increase in electrical energy demand by 11.22%, and electrical power 5.52%.